2016
DOI: 10.1103/physrevd.94.064004
|View full text |Cite
|
Sign up to set email alerts
|

A tensorial description of particle perception in black-hole physics

Abstract: In quantum field theory in curved backgrounds, one typically distinguishes between objective, tensorial quantities such as the renormalized stress-energy tensor (RSET) and subjective, nontensorial quantities such as Bogoliubov coefficients which encode perception effects associated with the specific trajectory of a detector. In this work, we propose a way to treat both objective and subjective notions on an equal tensorial footing. For that purpose, we define a new tensor which we will call the perception reno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…We also found that, after including the term capturing the effects of non-exact adiabaticity of the temperature functional, the discrepancy with the energy density obtained from the RSET increased in magnitude. One might think that this is contradictory as the energy density considered in (29) closely resembles the energy density computed from the RSET in [21], but this is not the case. This can be accounted for by the fact that the quantity computed in [21] is not the same energy density for the freely-falling observer as we computed in (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also found that, after including the term capturing the effects of non-exact adiabaticity of the temperature functional, the discrepancy with the energy density obtained from the RSET increased in magnitude. One might think that this is contradictory as the energy density considered in (29) closely resembles the energy density computed from the RSET in [21], but this is not the case. This can be accounted for by the fact that the quantity computed in [21] is not the same energy density for the freely-falling observer as we computed in (13).…”
Section: Discussionmentioning
confidence: 94%
“…Throughout the paper we considered the case of black hole collapse and worked with Unruh vacuum state. For this case, unlike[21], we do not need to consider the contribution of the effective temperature with respect to the ingoing null coordinate to the energy density.…”
mentioning
confidence: 99%
“…As already mentioned in the introduction, in this work we shall propose a clean separation between the Hawking and Unruh effects (under the simplifying assumptions of the analysis). This separation amounts to distinguishing between radiation action as the Hawking effect, and radiation back-reaction as the Unruh effect (an interpretation which we already advanced in [22]-see also [23]). In the first case, it is the radiation emitted by the black hole and already present in the field which acts upon the detector; while in the second, it is the detector that perturbs the field and, by back-reaction, modifies its trajectory at the same time that it becomes excited.…”
Section: Hawking Versus Unruh Effectsmentioning
confidence: 92%
“…This is a generalisation of the Hawking temperature which characterises the flux of outgoing radiation at future infinity. As was shown in [23], this function is directly related to the term in the RSET evaluated in dynamical vacua which regularises the divergence at the horizon of the static Boulware vacuum.…”
Section: Introductionmentioning
confidence: 75%
“…In more general terms, if κ ũ u or κ ṽ v remain constant for a sufficiently long period of time (defined by an adiabaticity condition), the vacuum state defined by the {ũ,ṽ} coordinates (through the modes in (2)) will be seen by an observer with proper coordinates {u, v} as a thermal state of outgoing or ingoing radiation respectively [22]. This function is also directly related to the outgoing and ingoing radiation fluxes which appear in the RSET after a change of vacuum state [23]. Specifically, equations (5) can be written as…”
Section: Renormalised Stress-energy Tensor In 1+1 Dimensionsmentioning
confidence: 99%